Cultural capital and reproduction of the intelligence gap - N. Razeghi; M. Sharepour; F. Akhondzade (Taḥqīqāt-i Farhangī-i Īrān, 2021)
An ever-increasing digital divide around the globe has turned into one of the greatest challenges to several areas of the information society with direct and indirect consequences. This has also increased the demand for more research in this field. This study, which is based on Bourdieu's cultural capital reproduction theory, is an attempt to answer the question as: To what extent individuals' cultural capital affects the digital gap among them? The survey method was applied in this research where a questionnaire was used to collect the data. The population of the study consisted of 183,198 youths from the city of Bābol (Mazandaran, Iran) aged 18-29 years. The sample size was estimated to be 385 by Cochran formula. The data were then collected randomly in a multistage cluster sampling from 8 areas in the above city. The results showed that there is a digital divide among people with different cultural capitals. The results of multiple regression analysis showed that the objectified dimension of the cultural capital (β = 0.472), the embodied dimension (β = 0.41) and the institutionalized dimension (β = 0.20) had the greatest effect on the people's digital divide. The results also showed that the independent variable of the research, i.e. cultural capital, explained about 0.26 percent of the variance of the dependent variable, i.e. the digital divide.